Delayed Establishment of Gut Microbiota in Infants Delivered by Cesarean Section - Kim, Gyungcheon; Bae, Jaewoong; Kim, Mi Jin; Kwon, Hyeji; Park, Gwoncheol; Kim, Seok-Jin; Choe, Yon Ho; Kim, Jisook; Park, Sook-Hyun; Choe, Byung-Ho; Shin, Hakdong; Kang, Ben (Frontiers in Microbiology, 2020)
The maternal vaginal microbiome is an important source for infant gut microbiome development. However, infants delivered by Cesarean section (CS) do not contact the maternal vaginal microbiome and this delivery method may perturb the early establishment and development of the gut microbiome. The aim of this study was to investigate the early gut microbiota of Korean newborns receiving the same postpartum care services for two weeks after birth by delivery mode using fecal samples collected at days 3, 7, and 14. Early gut microbiota development patterns were examined using 16S rRNA gene-based sequencing from 132 infants either born vaginally (VD, n = 64) or via Cesarean section (CS, n = 68). VD-born neonates showed increased alpha diversity in infant fecal samples collated at days 7 and 14 compared to those from day 3, while those of CS infants did not differ (p < 0.015). Bacterial structures of infants from both groups separated at day 7 (p < 0.001) and day 14 (p < 0.01). The bacterial structure of VD infants gradually changed over time (day 3 vs. day 7, p < 0.012; day 3 vs. day 14, p < 0.001). Day 14 samples of CS infants differed from day 3 and 7 samples (day 3 vs. day 14, p < 0.001). VD infant relative abundance of Bifidobacterium (days 7, 14), Bacteroides (days 7, 14), and Lachnospiraceae (day 7) significantly increased compared to CS infants, with a lower abundance of Enterobacteriaceae (found in all periods of the CS group) (LDA > 3.0). Relative abundances of Bifidobacterium, Lactobacillus, and Staphylococcus were significantly increased in both VD and CS groups at day 14 (LDA > 3.0). Predicted functional analysis showed that VD infants had overrepresented starch/sucrose, amino acid and nucleotide metabolism in gut microbiota with depleted lipopolysaccharide biosynthesis until day 14 compared to CS infants. This study confirmed that delivery mode is the major determinant of neonatal intestinal microbiome establishment and provides a profile of microbiota perturbations in CS infants. Our findings provide preliminary insight for establishing recovery methods to supply the specific microbes missing in CS infants.